IMPROVING THE METHODOLOGY OF STATE FINANCIAL CONTROL OVER THE BUDGET PROCESS (World Economics and Finance Bulletin, 2024)
The article examines ways to improve the methodical provision of state financial control over the budget process. In addition, proposals for the development of standardization of state financial control in the short, medium and long-term perspective have been developed
Keywords: State budget; budget process; tax